Development of Teaching Skills of Early Childhood Teachers under the Office of Private Education with the EF GUIDELINE Tool in Roi Et and Yasothon Province - Suebsing, Saksri; Udomsun, Nitinard; Boonpok, Supimol (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to; 1) develop the teaching skills of early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces with the EF GUIDELINE tool, 2) compare the development of teaching skills of early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces with the EF GUIDELINE tool, and 3) study the opinions of early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces towards teaching skills with the EF GUIDELINE tool. The sample group was early childhood teachers under the Office of Private Education in Roi Et and Yasothon Provinces the first semester of the academic year 2021 consisted of 100 students who were obtained by selective sampling. The tools used include a Handbook of learning activities, quizzes, and opinion questionnaires. The statistics used in the research were mean, standard deviation, and Paired t–test. The results of the research were as follows: 1) Early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces with the tools EF GUIDELINE had the ability on teaching skills overall at a moderate level, i.e. activities of flower patterns and colors, cute photo book activities, and tie-dye activities with bright colors. 2) Early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces, the mean scores after organizing learning activities about developing teaching skills with EF GUIDELINE were higher than before organizing learning activities with statistically significant at the .01 level. and 3) Early childhood teachers under the Office of Private Education in Roi Et and Yasothon provinces The overall level of teaching skills with EF GUIDELINE tools is at the highest level.